2006
DOI: 10.1002/jnr.21140
|View full text |Cite
|
Sign up to set email alerts
|

Acute, chronic and withdrawal effects of the cannabinoid receptor agonist WIN55212‐2 on the sequential activation of MAPK/Raf‐MEK‐ERK signaling in the rat cerebral frontal cortex: Short‐term regulation by intrinsic and extrinsic pathways

Abstract: The cannabinoids (CB) modulate the extracellular signal-regulated kinase (ERK), leading to various forms of plasticity in the brain. Little is known, however, on the in vivo short- and long-term activation and regulation of the components of mitogen-activated protein kinase (MAPK)/ERK signaling by CB. The CB agonist WIN55212-2 (8 mg/kg) increased the immunodensities of phosphorylated c-Raf-1 (42%), MEK1/2 (63%), ERK1 (24%), and ERK2 (28%) in the rat cerebral frontal cortex. These effects were antagonized by SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
(96 reference statements)
2
14
0
Order By: Relevance
“…These effects may explain our findings on the reduction of cerebral edema in the AraS-treated mice. In addition, CB1 receptor agonists were shown to activate Akt (Gomez del Pulgar et al, 2000) and ERK (Moranta et al 2007), which participate in prosurvival processes, including those related to neuroprotection (Pignataro et al, 2008;Yune et al, 2008). Our present results, in agreement with those of Milman et al (2006), suggest that in the brain, as in endothelial cells, the novel The effect of AraS treatment on caspase-3 activity (expressed as fluorescence units of DEVD-AFC cleaved product) in the brains of shamoperated controls and CHI animals treated with vehicle, AraS, AraS + SR141716A, AraS + SR144528, or AraS + capsazepine 72 hours after injury (&P < 0.05 versus AraS, ## P < 0.01 versus vehicle, ***P < 0.001 versus sham).…”
Section: Discussionmentioning
confidence: 99%
“…These effects may explain our findings on the reduction of cerebral edema in the AraS-treated mice. In addition, CB1 receptor agonists were shown to activate Akt (Gomez del Pulgar et al, 2000) and ERK (Moranta et al 2007), which participate in prosurvival processes, including those related to neuroprotection (Pignataro et al, 2008;Yune et al, 2008). Our present results, in agreement with those of Milman et al (2006), suggest that in the brain, as in endothelial cells, the novel The effect of AraS treatment on caspase-3 activity (expressed as fluorescence units of DEVD-AFC cleaved product) in the brains of shamoperated controls and CHI animals treated with vehicle, AraS, AraS + SR141716A, AraS + SR144528, or AraS + capsazepine 72 hours after injury (&P < 0.05 versus AraS, ## P < 0.01 versus vehicle, ***P < 0.001 versus sham).…”
Section: Discussionmentioning
confidence: 99%
“…Control mice received drug vehicle (Cremophor : ethanol : water, 1:1:18 proportion or DMSO : Tween 80 : water, 1:1:8 proportion; 2 mL·kg −1 , i.p., 1 h). The doses of WIN55,212‐2, rimonabant and JWH133 were chosen from earlier studies (Moranta et al ., 2007; see also Barna et al ., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For the chronic treatment with WIN55212‐2, groups of mice were injected (i.p.) twice daily for 5 days with increasing doses of the agonist (1–8 mg·kg −1 ; Moranta et al ., 2007). The first group of mice was killed 1 h after the last dose of WIN55212‐2 to assess the brain content of target proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maresz et al ., 2007; Zhang et al ., 2007; Fernandez‐Ruiz et al ., 2008) and neurogenesis (Galve‐Roperh et al ., 2007). It was also suggested that CB 1 receptors activate intracellular mechanisms such as the phosphatidylinositol 3‐kinase (PI3K/Akt) (Gomez Del Pulgar et al ., 2002; Molina‐Holgado et al ., 2005; Ozaita et al ., 2007) and ERK (Valjent et al ., 2001; Derkinderen et al ., 2003; Tonini et al ., 2006; Moranta et al ., 2007) pathways that are considered as survival signals and may contribute to the protective effects of CBs. Other neuroprotective mechanisms of CBs in either healthy or pathologic conditions were also suggested (for recent reviews, see Pacher et al ., 2006; Di Marzo, 2008; Fowler et al ., 2010; Viscomi et al ., 2010).…”
Section: Neuroprotective Effects Of Cbs In Acute Brain Injuriesmentioning
confidence: 99%